Changing of IKZF1 genotype during Philadelphia-negative precursor-B acute lymphoblastic leukemia progression: a short clinical report. (2016) - Vshyukova, Volha; Meleshko, Alexander; Mihal, Natalia; Aleinikova, Olga
Highlights: The case demonstrated a rare event of clonal heterogeneity by IKZF1 gene status in BCRABL1- ALL. IKZF1 deletions are secondary events in ALL caused by clonal evolution during the treatment. It's prognostic significance could be more crucial in BCR-ABL- rather than in BCR-ABL + ALL. IKZF1 gene alterations may be determined and proved at the genome, expression and protein level. IKZF1 deletions are suitable for MRD detection but not stable compared to Ig/TCR rearrangement.